How exercise frequency affects BMI: a nationwide cross-sectional study exploring key influencing factors, including dietary behavior - Zhang, Ming; Guan, Qinyi; Mai, Jianrong; Li, Si; Liu, Chengwu; Zhou, Ling; Lin, Lina; Teng, Kaisheng (Frontiers in Public Health, 2025)
PurposeBody Mass Index (BMI) is an important indicator for assessing obesity and related health risks. With the rapid socio-economic development and changes in lifestyle, abnormal BMI (such as underweight, overweight, and obesity) has become an increasingly serious public health issue. This study aims to explore the impact of exercise frequency on BMI among Chinese adults aged 19 to 59, and to analyze the role of dietary behaviors in regulating BMI, providing a basis for BMI intervention strategies.MethodThe study employs a multi-stage sampling method across 23 provinces, provincial capitals, and four municipalities in China, randomly selecting 120 cities from each region. Online surveys were conducted using Wenjuanxing by trained surveyors.ResultA total of 8,611 individuals participated in the survey. Among them, 1,066 (12.38%) had a BMI < 18.5, 5,354 (62.18%) had a BMI between 18.5 and 23.9, and 2,191 (25.44%) had a BMI ≥ 24. Factors such as gender, age, marital status, monthly household income, smoking, and alcohol consumption significantly affected BMI (p < 0.05). The overall impact of exercise on abnormal BMI was −0.003, with a direct effect of −0.005. The mediating effect of dietary behaviors between exercise and abnormal BMI was 0.002, accounting for 92.48% of the total effect.ConclusionThis study highlights the widespread prevalence of abnormal BMI among individuals aged 19 to 59 in China. A single exercise intervention may be insufficient to effectively improve abnormal BMI; thus, it should be combined with strategies aimed at enhancing dietary behaviors.